If you were to think of this diagram as a map of intersecting roads, corresponding angles are the ones on the same corner:
NW corner: ∠1 and ∠3
NE corner: ∠5 and ∠7
SE corner: ∠6 and ∠8
SW corner: ∠2 and ∠4
The choices in bold font above are the only pairs of corresponding angles that are in your answer list:
∠1 and ∠3∠5 and ∠7∠6 and ∠8Answer:
∠1 and ∠3 , ∠6 and ∠8 , ∠5 and ∠7 are corresponding angles
Step-by-step explanation:
Corresponding Angles are angles which occupy same relative position at intersection when a line intersects two lines.
In pair of corresponding angles, one angle is interior angle and other one is exterior angle.
Option 1:
∠1 is exterior angle and ∠3 is interior angle. Also Both are at relatively same position.
Thus they are Corresponding angles.
Option 2:
∠6 is interior angle and ∠8 is exterior angle. Also Both are at relatively same position.
Thus they are Corresponding angles.
Option 3:
∠2 and ∠8 both are exterior angle.
Thus they are not Corresponding angles.
Option 4:
∠5 is interior angle and ∠7 is exterior angle. Also Both are at relatively same position.
Thus they are Corresponding angles.
Option 5:
∠2 and ∠7 both are exterior angles.
Thus they are not corresponding angles.
Option 6:
∠3 and ∠6 both are interior angles.
Thus they are not corresponding angles.
What is the value of y in the solution to the following system of linear equations?
2x+2=y
2y=5x-1
A) 3
B) 5
C) 8
D) 12
ANSWER
[tex]y=12[/tex]
EXPLANATION
One way is to make x the subject in one equation and substitute into the other.
[tex]2x+2=y[/tex]
[tex]\Rightarrow 2x=y-2[/tex]
[tex]\Rightarrow x=\frac{y}{2}-1--(1)[/tex]
The second equation is
[tex]2y=5x-1--(2)[/tex]
Let us put equation 1 in 2
[tex]\Rightarrow 2y=5(\frac{y}{2}-1)-1[/tex]
[tex]\Rightarrow 2y=\frac{5y}{2}-5-1[/tex]
[tex]\Rightarrow 2y=\frac{5y}{2}-6[/tex]
Multiplying through by 2 gives;
[tex]\Rightarrow 4y=5y-12[/tex]
[tex]\Rightarrow 4y-5y=-12[/tex]
[tex]\Rightarrow -y=-12[/tex]
[tex]\Rightarrow y=12[/tex]
D
given the 2 equations
2x + 2 = y → (1)
2y = 5x - 1 → (2)
Substitute y = 2x + 2 into (2)
2(2x + 2) = 5x - 1
4x + 4 = 5x - 1 ( subtract 5x from both sides )
- x + 4 = = - 1 ( subtract 4 from both sides )
- x = - 5 ( multiply through by - 1 )
x = 5
substitute x = 5 into (1)
y = (2 × 5 ) + 2 = 10 + 2 = 12 → D
If i leave my house at 6:52 am and run 1 mile at an easy pace (8:15 per mile), then 3 miles at tempo (7:12 per mile) and 1 mile at easy pace again, what time do i get home for breakfast?
Running 2 miles at 8:15 per mile takes 16:30 minutes.
Running 3 miles at 7:12 per mile takes 21:36 minutes.
The total running time is 16:30 + 21:36 = 38:06 minutes. That length of time after 6:52 am is 7:30:06 am.
You get home for breakfast at 6 seconds past 7:30 am.
By adding the times spent on each individual run to your start time, you should arrive home at approximately 7:30 am.
Explanation:To begin with, this is a question about time calculation, where you need to know exactly how to calculate time durations. First, you start running at 6:52 am. Your easy pace is 8 minutes 15 seconds, or 8.25 minutes, per mile and you do this once before and once after your tempo run. So, for 2 miles, it's 2*8.25 = 16.5 minutes.
Then you have a tempo pace at 7 minutes 12 seconds, or 7.2 minutes, per mile. You run 3 miles at tempo pace, so that's 3*7.2 = 21.6 minutes.
Adding these two results together, you have a total running time of 38.1 minutes (16.5 minutes easy pace + 21.6 minutes tempo pace). Adding this to your start time of 6:52 am gives you a rough end time of 7:30 am. Please note that this estimation rounds your running time to the nearest minute.
Learn more about time calculation here:https://brainly.com/question/34080240
#SPJ2
Graph f(x)=12x+2.
Use the line tool and select two points to graph the line.
Answer:
(0,2) and (1,14)
Graph is attached.
Step-by-step explanation:
Let us find y intercept
When x=0, y = f(x) =2
Hence one point is (0,2)
Other point is let x = 1,
y =12(1)+2 =14
(1,14) (0,2) are plotted and joined.
Graph is attached.
At 3:00 p.m., Jasmine leaves her house and drives north to her parent’s home. She arrives at 6:00 p.m. Also leaving at 3:00 p.m. from Jasmine’s house is her friend Jewel who leaves and drives south to her parent’s home. She arrives at 5:00 p.m. The driving distance between both parents’ homes is 300 mi. Jasmine and Jewel drove at the same speed. What was their speed? *
I think you need to think about the problem carefully. My guess is 1,that's my guess. sorry i couldn't give an accurate answer or you divide 300 by 5
Answer:
60
Step-by-step explanation:
Solve the problem using the previous balance method.
The account balance on April 1st is $60.15.
On April 15th a payment of $51.00 is made.
On April 25th a purchase of $91.27 is made.
What is the finance charge if the annual rate is 18%?
What is the new account balance?
Finance charge = $ ____
New balance = $ ____
Annual Percent Rate (APR) = 18%
Rate during the current billing cycle = 18/12 = 1.5%
Balance at the beginning of the billing cycle = 60.15
Payment 51.00
Balance 10.15
Purchase 91.27
Balance - 81.12
Finance Charge 60.15 * 0.015 = 0.90
New Balance - 82.02
when multipling signed numbers how do you know wether the number is positive or neagitive
If an odd number of minus signs are involved in a product or quotient, the sign of the result is negative. Otherwise, it is positive.
Examples:
(-1)(-1) = 1
(-1)(-1)(-1) = -1
(-1)/(-1) = 1
(-1)(-1)/(-1) = -1
The product of two positive numbers is positive: (+)(+) = (+).
The product of one positive number and one neg number is neg: (+)(-) = (-).
The product of two negative numbers is positive: (-)(-) = (+)
At the annual dog show chantel noticed that there were 3 more scotties than schnauzers. She also realized that the number of wirehaired terriers was 5 less than the number of schnauzers. If there were 78 dogs in all ( counting schnauzers scotties and terriers) how many schnauzers were there? Write and solve equation
x + x - 3 + 2x - 3 = 78
4x = 84
x = 21
Answer: 21 Schnauzers.
there are 200 students in the 7th grade 98% of the students in the greater going on the field trip how many students are going on the field trip show your work and I will mark brainiest
30 percent
22% of 200 is 44, 44 students play football
12 of 200 is 24, 24 students play baseball
44+24=68
The teams have a total of 68 players
because 8 play both sports you subract 8
68-8=60
The answer is a tolal of 60 students play sports
I think the answer is 60
Find the unknown length of y. Please help ASAP!!!!!!!! :(
We assume the slope is a constant, so the rise is proportional to the run.
... y/(4 ft) = (31 ft)/(3 ft)
... y = (4/3)·(31 ft)
... y = 41 1/3 ft = 41 ft 4 in
1000m divided by 100n can be written in the form 10z. Express z in terms of m and n
Answer:
[tex]10 ^ {3m-2n} = 10 ^ z[/tex]
Where z = 3m-2n
Step-by-step explanation:
An important mathematical property about the powers is that when powers of equal base are divided, the same base is placed and the exponents are subtracted.
Then we can write 1000m and 100n as powers of the same base:
[tex]1000 ^ m = (10 ^ 3) ^ m = 10 ^ {3m}\\ 100 ^ n = (10 ^ 2) ^ n = 10 ^ {2n}[/tex]
Now we perform the division of powers of the same base (10)
[tex]\frac{10 ^ {3m}}{10 ^ {2n}} = 10 ^ {3m-2n}[/tex]
Finally
[tex]10 ^ {3m-2n} = 10 ^ z[/tex]
Where z = 3m-2n
To express z in terms of m and n, rewrite the equation: 1000m / 100n = 10z. Then, simplify to 100m / 10n = z. So, z can be expressed as 10m/n.
Explanation:The given equation is 1000m divided by 100n equals to 10z. To express z in terms of m and n, we need to isolate z. Let's proceed step by step:
First, rewrite the equation: 1000m / 100n = 10z;Then, eliminate the 10 on the right side by dividing both sides by 10, we get: 100m / 10n = z; Then, simplify the left side, we get: 10m/n = z;So, z can be expressed as 10m/n.
Learn more about Algebraic Expression here:https://brainly.com/question/953809
#SPJ2
Many medications are determined by the weight of the patient in kilograms. When a patient’s weight is measured in pounds, the doctor must then convert the weight to kilograms. The table shows conversions for common units of weight.
Answer:
70.2
Step-by-step explanation:
Multiply the weight in pounds by the conversion factor.
[tex]156\,lb\times\dfrac{0.45\,kg}{1\, lb}=70.2\,kg[/tex]
Answer:
70.2 kilograms
Step-by-step explanation:
In order to calculate this you just have to do a rule of three, where you use the equivalence of the pounds by the kilograms, in the table you see that 1 pound equals .45 kilograms, so you use that for your equivalence:
[tex]\frac{1pound}{.45kilograms}= \frac{156 pounds}{x}[/tex]
[tex]x=\frac{165*.45}{1 pound}[/tex]
[tex]x=70.2 kilos[/tex]
So we know that the patient weights 70,2 kilograms.
What is the value of the expression (9+15) divided by 3 plus 2
Hey!
This question is super easy to me. This question is going to be used their order of operations.
Order of operations stands for
↓
P-Parenthesis
E-Exponents
M-Multiply
D-Divide
A-Add
S-Subtract
(9+15)/3+2
24/3+2
8+2
=10
Answer⇒⇒⇒⇒⇒=10
Hope this helps!
Thank you for posting your question at here on Brainly.
-Charlie
Answer:
10
Step-by-step explanation:
(9+15) ÷ 3 + 2 = 10
help please! thanks!
Answer:
The edge length of the storage cube is 30 centimeters.
Step-by-step explanation:
All sides/edges of a cube has equal length.
Let's take the length of a edge as [tex]a[/tex] centimeters.
The volume a the cube = Height * Width * Length
All height, width and length are equal([tex]a[/tex] centimeters).
Now we can write the equation again as,
The volume a the cube = [tex]a*a*a[/tex]
Volume of the cube is given as 27,000 cubic centimeters.
Therefore,
[tex]a*a*a=27,000[/tex]
[tex]a=\sqrt[3]{27,000}[/tex]
[tex]a=30[/tex]
Therefore, the edge length of the storage cube is 30 centimeters.
Daniela bought a car for $24,000. Each year the value of the car decreases by $1750. a. Write a function that shows the value of the car after y years.
I hope this might be able to help you.
Since the value of the car slowly decreases each year and each year is represented by y, the function is 24,000-1750y=f(x).
Which ordered pairs are solutions to the inequality −2x+y≥−4 ?
Select each correct answer.
(0, −5)
(3, −1)
(1, −2)
(0, 1)
(−1, 1)
Answer:
(0,-5) , (1,-2) , (0,1) and (-1,1)
Step-by-step explanation:
-2x + y ≥ -4
y ≥ 2x - 4
Taking a point (0,-5):
-5 ≥ 0 - 4 , 5 ≥ -4
This situation is true.
Taking a point (3,-1):
-1 ≥ 2(3) - 4 , -1 ≥ 2
This situation is not true.
Taking a situation (1,-2):
-2 ≥ 2(1) - 4 , -2 ≥ -2
This situation is true.
Taking a point (0,1):
1 ≥ 0 - 4 , 1 ≥ -4
This situation is true.
Taking a point (-1,1):
1 ≥ 2(-1) - 4 , 1 ≥ -6
This situation is true.
The correct answers are
(−1, −1)
(5, −12)
(0, 1)
Have a nice day!
Anyone good with Literal Expressions?
Answer:
[tex]\boxed{F=\dfrac{9}{5}c+32}[/tex]
Step-by-step explanation:
[tex]\dfrac{5(F-32)}{9}=c\qquad\text{multiply both sides by 9}\\\\5(F-32)=9c\qquad\text{divide both sides by 5}\\\\F-32=\dfrac{9}{5}c\qquad\text{add 32 to both sides}\\\\\boxed{F=\dfrac{9}{5}c+32}[/tex]
Check out the attachment
The graph of the tangent function approaches vertical asymptotes at x=±π/2. The inverse function will have horizontal asymptotes of y=±π/2. The only viable choice among your graphs is ...
... Graph C
_____
The graph of the inverse of a function is the function's graph with the x- and y-coordinates swapped. Essentially, the graph is reflected across the line y=x. The graph of the tangent function has a vertical aspect. Its inverse has a horizontal aspect.
Quick!!! I need to do my homework
Solve: x - 1 < 3
x < 4
given x - 1 < 3 ( add 1 to both sides )
x < 4
or x ∈ ( - ∞, 4 ) ← in interval notation
Please Help ASAP 20 points
Find the slope of the line through the given points.
(−1, 2) and (−5,10)
(1,3) and (0,−9)
(18, 6) and (−7, 7)
(−7, 10 ) and (1, 10)
Write the equation of the line parallel to the given line and passing through the given point.
y=2x−8 through (3,10)
Copy down y = 2x - 8. Note that any line parallel to this will have exactly the same form, although the constant (representing the y-intercept) may be different.
Knowing that this line passes through (3,10), all we have to do is find the value of the constant of this new, parallel line. Substitute 10 for y and 3 for x, obtaining 10 = 2(3) + b. Then 10-6 = b, or b = 4, and:
y =2x + 4 (answer). Again, note how the form of this new equation is exactly the same as the form of the given equation; only the constant (the y-intercept) is different.
Answer:
y=2x+4
Step-by-step explanation:
The equation we have is y=2x-8, so we subsitute the values and 8 is equal to b. After you substitue you solve it. b=4. So, the answer is y=2x+4
Hope this helped :) *also sorry if I spelled some words wrong*
P = 215 (1.005)t/3 the equation above can be used to model the population, in thousands, of a certain city t years after 2000. according to the model, the population is predicted to increase by 0.5% every n months. what is the value of n
As t/3 it means that 0.5% every 3 years.
So n will be 3 years , 36 months
Solution:
The Given model to Predict the population
[tex]P=P_{0}(1.005)^{\frac{t}{3}[/tex]
----------------------------------(1)
The population increases by 0.5 % every n months.
Initial Population = 215
Final Population
[tex]=215+215\times \frac{0.5}{100}\\\\=215+1.075\\\\=216.075[/tex]
Substituting the value of , Initial and final Population in equation 1,
[tex]216.075=215\times (1.005)^{\frac{t}{3}}\\\\ (1.005)^{\frac{t}{3}}=\frac{216.075}{215}\\\\ (1.005)^{\frac{t}{3}}=(1.005)^{1}\\\\ \frac{t}{3}=1\\\\ t=3[/tex]
t=3 years =36 months
The value of n is equal to 36 months.
X+3x-2=6x-12 please help
Can anyone transform a vertex form equation into a standard form?
y= -0.3(x-0)^2+3
If you can show work.
the standard form of a quadratic is : y = ax² + bx + c : (a ≠ 0 )
note that (x - 0 )² = x²
distributing by - 0.3 gives
y= - 0.3x² + 3 ← in standard form
with a = - 0.3, b = 0 and c = 3
Pls help will mark brainliest
4x+2y=6
x-3y=5
SOLVE BY ELIMINATION METHOD PLS
Answer:
y=-1
Step-by-step explanation:
The first step to solving this problem is to write it out like this-->
4x+2y=6
x-3y=5
Next you want to eliminate the X's or the Y's, I chose to elininate the X's-->
4x+2y=6
-4(x-3y=5) [You MUST distribute the -4 to each of the numbers in the equation]
Then you get--->
4x+2y=6
-4x+12y=-20 Then you add them top to bottom--->
0x+14y=-14 [At this point you dont have to write the X]Next you solve for y-->
14y=-14 Divide both sides by 14, in order to get the y by itself-->
y=-1 And theres your answer hope it helps :D
we have the 2 equations
4x + 2y = 6 → (1)
x - 3y = 5 → (2)
multiply (2) by 4
4x - 12y = 20 → (3)
(3) - (1) to eliminate the terms in x
- 14y = 14 ( divide both sides by - 14 )
y = - 1
substitute y = - 1 into (1) and solve for x
4x - 2 = 6 ) add 2 to both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is x = 2, y = - 1
A number, n, is multiplied by -3/8. The product is -0.1. What is the value of n?
Rewriting this symbolically, (-3/8)n = -0.1. Let's solve for n. To do this, multiply both sides of the equation by (-8/3). This results in n = 8/30, or n= 4/15.
Use the identity x^3+y^3+z^3−3xyz=(x+y+z)(x^2+y^2+z^2−x^y−y^z−z^x) to determine the value of the sum of three integers given:
the sum of their squares is 110,
the sum of their cubes is 684,
the product of the three integers is 210,
and the sum of any two products (xy+yz+zx) is 107.
Correctly written, your identity would tell you ...
... (sum of cubes) - 3·(product) = (sum of integers)·((sum of squares) - (sum of any two products))
Filling in the given numbers, you have ...
... 684 - 3·210 = (sum of integers)·(110 -107)
... 54 = (sum of integers)·3 . . . . . simplify
... sum of integers = 54/3 . . . . . . divide by the coefficient of the variable
... sum of integers = 18
_____
Integers 5, 6, and 7 meet these conditions.
need help finding the x, y, and z. please and thank you
The first step in any problem is to look at what you are given. When solving systems of linear equations, it is often helpful to eliminate one or more of the variables by adding or subtracting a multiple of one equation with a multiple of another. It is convenient when at least one of the multipliers is 1.
Here, we can cancel the y-terms in the 2nd and 3rd equations simply by adding them together. This gives
... (5x +y -4z) +(-3x -y +5z) = (41) +(-45)
... 2x +z = -4 . . . . simplified
Likewise, we can add 3 times the second equation to the first to cancel y in that sum.
... 3(5x +y -4z) +(2x -3y +z) = 3(41) + (-1)
...15x +3y -12z +2x -3y +z = 123 -1
...17x -11z = 122 . . . . simplified
Now that we have 2 equations in x and z, we can go through the same process. We observe that the coefficient of z is +1 in the first equation and -11 in the second. The means we can cancel the z terms by adding 11 times the first equation to the second:
... 11(2x +z) +(17x -11z) = 11(-4) +122
...22x +17x = 78 . . . . . . simplify a little bit
... x = 78/39 = 2 . . . . . . divide by 39
From above, we find
... z = -4 -2x = -4 -2·2 = -8
... y = 41 -5x +4z = 41-5(2) +4(-8) = 41 -42 = -1
The solution is (x, y, z) = (2, -1, -8).
_____
The method of elimination used here will vary with the system of equations. If you want to employ a consistent method, you can use Cramer's Rule, Gaussian elimination, or matrix methods. Since you apparently don't mind help from technology, learning to do this on your graphing calculator can also be a good idea.
1. Refer to the equation 2x − 6y = 12.
(a) Create a table of values for at least 4 points. Show your work.
(b) Use the table of values to graph the line. Use a straightedge or ruler to draw the line.
Answer:
Answer:
x 6 0 3 -3
y 0 -2 -1 -3
Step-by-step explanation:
We substitute x value in the equation and find y.
When x =0, -6y = 12 or y =-2
Likewise all pairs are found out.
Similarly put y =0: x = 6
When x =3, 2(3)-6y =12 :y =-1
When x=-3, 2(-3)-6y=12 or y = -3
Plot these on a graph and join the line.
Graph is attached below:
a. 2x-6y=12: y = (12-2x)/6.
b. Graph the line using (0,2) and (3,0).
(a) To create a table of values for at least 4 points, we can solve the equation for y in terms of x:
y = (12 - 2x) / 6
We can then choose different values for x and plug them into the equation to find the corresponding y values.
Here is a table of values for at least 4 points:
x y
0 2
3 0
-3 4
6 -2
(b) To graph the line, we can use the two points from the table of values that are closest to each other.
In this case, we will use the points (0, 2) and (3, 0).
First, plot the two points on the coordinate plane.
Then, use a straightedge or ruler to draw a line that passes through both points.
Here is the graph of the line 2x − 6y = 12:
For similar question on Graph the line.
https://brainly.com/question/19040584
#SPJ3
Select the functions that have a value of -1. sin180° cos180° tan180° csc180° sec180° cot180°
We have to break each degree in terms of 90
A) [tex]sin180^\circ=sin(90\times2+0)[/tex]
Which is in third quadrant, therefore sine is negative hence
[tex]sin(90\times2+0)= -sin0 ^\circ = 0[/tex]
B) [tex]cos180^\circ =cos(90\times2+0)[/tex]
Which is in third quadrant, therefore cosine is negative hence
[tex]cos(90\times2+0)= -cos0^\circ = -1 [/tex]
C) [tex] tan180^\circ=tan(90\times2+0)[/tex]
Which is in third quadrant, therefore tangent is positive hence
[tex]tan(90\times2+0)= tan0^\circ = 0[/tex]
D) [tex]csc180^\circ=csc(90\times2+0)[/tex]
Which is in third quadrant, therefore cosec is negative hence
[tex]cosec(90\times2+0)= -csc0^\circ =[/tex]not defined
E)[tex]sec180^\circ=sec(90\times2+0)[/tex]
Which is in third quadrant, therefore secant is negative hence
[tex]sec(90\times2+0)= -sec0^\circ = -1 [/tex]
F) [tex] cot180^\circ=cot(90\times2+0)[/tex]
Which is in third quadrant, therefore tangent is positive hence
[tex]cot(90\times2+0)= cot0^\circ = [/tex] not defined
Hence only [tex] cos 180^\circ [/tex] and
[tex] sec180^\circ [/tex] have value -1
Hope this will help
Answer:
Cos and Sec
Step-by-step explanation:
thats the short of the guy above
To get the color dove-white, Ken mixed black paint and white paint in a ratio of 5:3. He used 20 gallons of black paint. How much white paint did he use?
12 gallons of white paint
divide 20 gallons by 5 to obtain 1 part of the ratio
[tex]\frac{20}{5}[/tex] = 4 gallons ← 1 part
white paint = 3 × 4 = 12 gallons ← 3 parts